Relationship Between Lifestyle and General Health Among Elderly People in Tehran - Akram Ghanbari Moghadam; Farahnaz Mohammadi Shahbolaghi; Asghar Dalvandi; Samane Hoseinzade (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: In future decade, the number of elder people is projected to increase and health promotion of this age group will be insufficient in the coming years. Recent geriatric research show, the elder mortality rate will increase with advancing age and inversely related to their life style status. In this descriptive study, we examined the relationship between elder life style and their general health status. Methods & Materials: We studied four hundred elder participants in five region of Tehran capital city with applying randomized multistage sampling of these geographical clusters in a cross-sectional research design. In this study, data was gathered by life style and general health questionnaires. The Life style questionnaire includes physical activity, nutrition, interpersonal, social, stress prevention and management subscales and general health was measured with 28 item General Health (GHQ) questionnaire. Results: According to the finding of this study, majority (95%) of Tehran elder population had a moderate lifestyle ranking and the results of multiple regression analysis show that there was a significant relationship between lifestyle dimensions and general health subscales. In this regard, we enface with a inverse significant relationship (P<0.01) between lifestyle and general health scores (r=-0.4). Conclusion: Moderate lifestyle ranking of elder in the region of study and especial demands of this growing population needs to further investigated and applying various strategies for promoting lifestyle changes, health and better elder quality of life.